CALCULATION OF THE ENERGY CONSUMPTION FOR DEFROSTING OF THE WOOD CHIPS - Deliiski, Nencho; Brezin, Veselin; Radkova, Izabela; Geffert, Anton; Geffertova, Jarmila; Tumbarkova, Natalia (Innovation in Woodworking Industry and Engineering design, 2015)
Аn approach for the calculation of the specific mass energy consumption (in kWh.t-1) needed for defrosting of the wood chips, which contain both frozen bound an free water, has been suggested. For the calculation of the a software program has been prepared in MS Excel 2010. With the help of the program calculations have been carried out for the determination of for oak, acacia, beech, and poplar frozen chips with moisture content in the range from u = 0.4 kg·kg-1 to u = 1.0 kg·kg-1 and with an initial temperature at the range from t0 = –40 oC to t0 = –1 oC. At temperature equal to –1 oC the defrosting process of the wood chips has been fully completed.